Vedic cosmology : creation ideas in the ancient Vedic religion : a hermeneutic study - Verma, Rajendra (New Delhi : New Age International, 1996)
Study based on Vedic literature.
Includes bibliographical references.
Keywords: Vedas; Hindu cosmology